Closure of oronasal communication using the use of palatal rotational flaps and platelet-rich fibrin (PRF): clinical case report - Pineda, Edgardo (2023)
Oronasal communication (OC) is a rare muco-osseous defect, especially in adults. This defect communicates the oral cavity directly with the nasal cavity. There are multiple surgical options for treatment, among which are the local palatal flaps, characterized by receiving their blood supply through the greater palatine artery. We present a case of closure of a OC of traumatic origin in an adult female patient, who had undergone surgery on three previous occasions without achieving definitive closure of the OC. The surgical technique used in this case was a palatoplasty through a double palatal flap plus the use of platelet-rich fibrin as a scar adjuvant, as it has the characteristic of reducing the healing time in lesions. A successful long-term closure of the OC was obtained, achieving an airtight closure, without tissue tension and maintaining the blood supply of the flap. This surgical technique can be replicated in different cases of muco-osseous defects, having minimal complication rates and sequelae in patients, besides being a simple technique and of only one operative time, if compared to other surgical techniques.